Nazwy cywilnej odzieży męskiej warstw niższych. Na materiale poznańskich listów gończych z lat 1816–1836 - Müller, Aneta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The article presents the lexical material concerning clothes vocabulary. The data was extracted from arrest warrants published from 1816 to 1836 in Publiczny Donosiciel ( Public Denunciator ) which was an annex to Dziennik Urzędowy Królewskiej Regencyi w Poznaniu ( Official Journal of the Royal Regency in Poznan ). The article presents the structure of the lexical and semantic field of NAMES OF CIVILIAN CLOTHES OF MEN’S FROM LOWER SOCIAL STRATA and its semantic and genealogical analysis. In this lexical and semantic field, 361 lexical items were classified, described and assigned to nine subfields which were then divided further. The genealogical analysis showed that a third of the vocabulary described are loanwords.